PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMUNIKASI ORGANISASI TERHADAP KINERJA KARYAWAN DAN ANGGOTA KEPOLISIAN RESOR KOTA PEKANBARU - Ramadhan, Putra; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The purpose of this research is to find out and analyze the effect of transformational leadership style on employee performance, to know and analyze the effect of organizational communication on employee performance, to know and analyze the influence of transformational leadership style and organizational communication simultaneously on employee performance. This study used explanatory quantitative research methods with sampling techniques in this study using random sampling and using the slovin formula which obtained a total of 85 respondents from 550 population of Employees and Members of the Pekanbaru City Police. The data collection technique uses a questionnaire which is then tested for validity and reliability. The data analysis technique in this study is a simple linear regression test and a determination test that is calculated using the SPSS for windows application. Based on the results of this study, it is known that the influence of transformational leadership style and organizational communication on employee performance is 28.7% while the remaining 71.3% is influenced by other factors. These other factors, one of which is ability which can affect employee performance. Keywords: transformational leadership style, organizational communication, employee performance